Governing geospatial aspects of smart destination development - The case of Novi Sad, Serbia - Radojević, Bojan; Stankov, Uglješa; Vujičić, Miroslav D. (Geographica Pannonica, 2023)
The development of smart cities and destinations heavily relies on geospatial technologies and intelligence. Geospatial aspects encompass location-based data and tools and are of significant importance in governing smart tourism destinations. This paper investigates the geospatial elements involved in the development of smart tourism destinations, by analyzing smart projects implemented in Novi Sad, Serbia. The theoretical framework draws upon the fields of geoinformatics, urban planning, and smart city development. Research conducted in Novi Sad reveals that the majority of smart initiatives, solutions, projects, and practices are geospatially oriented. To enhance the governing of smart cities, the paper introduces a comprehensive and adaptable catalogue of smart projects, which is easily navigable and comprehensible.
Keywords: geospatial aspects; smart tourism; smart tourism destination; smart projects; destination governance; Novi Sad